Student Experiences with Online Platforms: Critical Perspectives from Teaching and Learning of French as a Foreign Language (FFL) in Kenyan Universities - Auma, Rose; Mudogo, Benard; Kasili, Joyce; Miruka, Frida; Anyonje, Lydia (International Journal of Language Teaching and Education, 2023)
Limited empirical evidence is available in the context of teaching and learning French as a Foreign Language (FFL) as to whether the online platforms meet the needs of the learners. We seek to establish the needs and experiences of university students during the online teaching and learning of French as a foreign language (FFL) in sub-Saharan Africa, with specific focus on the Kenyan context. The results are based on three constructs; instructional materials, student support services and lecturers’ preparedness. A survey questionnaire was administered to 81 students in their third and final years of study in three universities in Western Kenya. The results demonstrate that students do not feel that the available online pedagogical practices meet their language competencies in learning FFL. Language policymakers must consider such results alongside local implementation resistance in implementing FFL online learning programs.